Epigallocatechin gallate and l-ascorbic acid in conjunction with modified atmospheric packaging preserve color and quality of refrigerated longtail tuna (Thunnus tonggol) slices - Suguna Palanisamy; Avtar Singh; Bin Zhang; Jong-Whan Rhim; Jun Tae Kim; Yu Fu; Soottawat Benjakul (Food Chemistry: X, 2025)
Discoloration and spoilage of tuna slices during refrigerated storage is the major problem associated with consumer's rejection. The aim of this study was to evaluate the effects of modified atmosphere packaging (MAP) including argon/oxygen: 90 %A/10 %O or nitrogen/oxygen: 90 %N/10 %O, which was employed individually or combined with epigallocatechin gallate/ascorbic acid (EGCG/AA) mixture (1:1, w/w) at 200 mg/kg on color and quality of longtail tuna slices stored at 4 °C for 120 h. EGCG/AA+ A/O MAP showed the least decline in a* value and oxymyoglobin content, while lipid and protein oxidation were significantly suppressed, followed by A/O MAP. EGCG/AA+A/O MAP lowered microbial growth as evidenced by lower total viable count (TVC), psychrophilic bacterial count, Pseudomonas spp., lactic acid bacteria, and presumptive Clostridium spp. counts than others (p < 0.05). EGCG/AA+A/O MAP exhibited high effectiveness in microbial inhibition and remained TVC below acceptable limit (5 log CFU/g), indicating the best condition for tuna treatment.